Hyperrealitas Iklan Perspektif Hukum Ekonomi Islam - Mursal Mursal; Neza Tessya Inggrit (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
Advertising is not just conveying information about a product (ideas, services and